Predicting Length of Hospital Stay Following Adult Cardiac Surgery: A Prospective Observational Study (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Despite life-saving benefits, adult cardiac surgery presents challenges due to potential for extended hospital stays and resource strain. Accurately predicting length of stay (LOS) is crucial for efficient resource allocation and patient discharge planning. The study aims to assess factors associated with LOS following adult cardiac surgery and proposed a model for predicting LOS after adult cardiac surgery.MATERIALS AND METHODS: A prospective observational study was conducted at Manmohan Cardiothoracic Vascular and Transplant Center from September 2019 to May 2021, enrolling 249 adults undergoing cardiac surgery. A prospective observational study was conducted at Manmohan Cardiothoracic Vascular and Transplant Center from September 2019 to May 2021, enrolling 249 adults undergoing cardiac surgery. Non-probability consecutive sampling was employed and a standardized data collection form was used to record patient-related, cardiacrelated, operation-related, and postoperative characteristics including LOS. Descriptive statistics and multivariate analysis were employed to meet the objectives.RESULTS: The study reported a median length of hospital stay as 10 days with interquartile range 6 days. Patients who experienced prolonged LOS (>13 days) after cardiac surgery accounted for 21.70% of the total sample. In an adjusted relationships, only female sex (AOR= 1.957; 95% CI: 1.022 - 3.745), previous cardiac surgery (AOR: 2.684, 95% CI: 1.314 - 7.885), active IE (AOR: 23.187, 95% CI: 2.467 - 217.969), and ECA (AOR: 3.891, 95% CI: 1.135 - 13.332) were identified as significant predictors of prolonged postoperative LOS.CONCLUSIONS: By understanding the factors influencing LOS following cardiac surgery, clinicians can optimize care plans and resource allocation, ultimately improving patient outcomes.